2020
DOI: 10.3390/nu12061605
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Acid Load with the Prevalence of Metabolic Syndrome among Participants in Baseline Survey of the Japan Multi-Institutional Collaborative Cohort Study

Abstract: The association between dietary acid load and metabolic syndrome (MetS) has not been fully investigated. A cross-sectional study was performed on 14,042 men and 14,105 women (aged 35–69 years) who participated in a baseline survey of the Japan Multi-Institutional Collaborative Cohort study. Dietary acid load was assessed using the net-endogenous-acid-production (NEAP) score that is closely correlated with the rate of renal net acid excretion. MetS was diagnosed according to the Joint Interim Statement Criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…Similar results were obtained by analyzing NEAP quartiles and MetS prevalence. These results are in agreement with previous reports indicating similar associations between PRAL as well as NEAP and the prevalence of MetS in Iranian patients with type 2 diabetes ( 40 ) and a cross-sectional Japanese study, in which higher NEAP values (PRAL was not calculated) were associated with an increased prevalence of MetS independently of sex, age, and BMI ( 17 ). Contradictory results were described by Jafari et al ( 41 ) who observed an association between MetS prevalence and NEAP but not PRAL in a cohort of Iranian men.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained by analyzing NEAP quartiles and MetS prevalence. These results are in agreement with previous reports indicating similar associations between PRAL as well as NEAP and the prevalence of MetS in Iranian patients with type 2 diabetes ( 40 ) and a cross-sectional Japanese study, in which higher NEAP values (PRAL was not calculated) were associated with an increased prevalence of MetS independently of sex, age, and BMI ( 17 ). Contradictory results were described by Jafari et al ( 41 ) who observed an association between MetS prevalence and NEAP but not PRAL in a cohort of Iranian men.…”
Section: Discussionsupporting
confidence: 93%
“…The concept that an acidic diet is associated with negative health outcomes is rampant among the public, but scientific evidence in this context remains to be consolidated and is mainly limited to the effect of DAL on bone mass and kidney stones. In fact, the effects of an acidic diet (with high PRAL values) on pathological conditions, such as hypertension, diabetes, and CV disease, are yet to be fully elucidated ( 13 , 14 ) and remain a matter of contention ( 15 17 ). While the MD has been widely demonstrated to elicit positive effects on cardiometabolic health ( 18 20 ) and may decrease DAL, it remains to identify a putative association between the MD and DAL, assessed using PRAL or NEAP.…”
Section: Introductionmentioning
confidence: 99%
“…The present study found a positive association between high DAL (NEAP score) with MetS. In line with the present findings, a cross‐sectional study by Arisawa et al on 14 042 Japanese men and 14 105 women (aged 35‐69 years) revealed higher DAL (NEAP score) was associated with a higher prevalence of MetS 28 . Iwase et al reported that higher DAL (PRAL and NEAP scores) was correlated with a higher prevalence of MetS in 149 patients with Type 2 diabetes 49 …”
Section: Discussionsupporting
confidence: 91%
“…In contrast to Farhangi et al, Wu et al showed a positive relationship between DAL and CRP 26,27 . Arisawa et al also reported that a higher acid load was associated with MetS 28 . In contrast, a study of 1430 Iranian adults found no significant association between MetS and quartiles of dietary acid load 29 …”
Section: Introductionmentioning
confidence: 89%
“…Median PRAL, NEAP F and NEAP R scores decreased significantly in the vegan intervention group ( Table 3 and Figure 1 ). These findings are of paramount importance, as a high DAL has been associated with a series of health repercussions [ 8 ], including an increased risk for cardiovascular disease [ 30 ], type-2-diabetes [ 31 ], metabolic syndrome [ 32 ], chronic kidney disease [ 33 ] and an elevated lipid accumulation product [ 34 ].…”
Section: Discussionmentioning
confidence: 99%